Dynamic calibration of slab track models for railway applications using full-scale testing. (February 2020) - Sainz-Aja, J.; Pombo, J.; Tholken, D.; Carrascal, I.; Polanco, J.; Ferreño, D.; Casado, J.; Diego, S.; Perez, A.; Filho, J. E. Abdala; Esen, A.; Cebasek, T. Marolt; et al.
Highlights: A detailed 3D slab track model that includes all components of the infrastructure. Full-scale tests of the slab track in high-speed and conventional speed operations. Full-scale tests of the fastening system in realistic service conditions. Identification of representative rail track models in realistic operation scenarios. Abstract: Research and development of technology for railways has found new impetus as society continues to search for cost effective and sustainable means of transport. This tasks engineers with using the state-of-the-art science and engineering for rolling stock development and advanced technologies for building high performance, reliable and cost-effective rail infrastructures. The main goal of this work is to develop detailed and validated three-dimensional slab track models using a finite element formulation, which include all components of the infrastructure. For this purpose, the parameters of the computational models are identified by performing full-scale tests of the fastening system and of the slab track, including all its material layers. The computational model proposed here is calibrated using this approach and a good agreement is obtained between experimental and numerical results. This work opens good perspectives to use this reliable track model to study the interaction with railway vehicles in realistic operation scenarios in order to assess the dynamic behaviour of the trains and to predict the long-term performance of the infrastructure and of its components.